Dynamic event types in frame semantics: the representation of change in FAMEu - Herweg, Michael (Heidelberg University papers on language & cognition, 2021)
This paper outlines an approach to representing concepts for dynamic situations in a frame-semantic format, using the example of motion verbs and their directional complements. It has been noted in recent research that traditional frames do not properly represent concepts that involve an element of change. A key ingredient of the present proposal is the notion of a phase array from phase-theoretical semantics as an additional frame attribute. A phase array serves to represent the internal temporal set-up of the situation described by a motion expression, as it is determined by the aspectual class of the verb and its projections. The components of the phase array are in turn interpreted using notions from dynamic logic. In this way, the frame receives a dynamic foundation which reflects different kinds of changes expressed by motion verbs and their directional complements. Building on that, a basic type system for motion verbs is introduced, augmented with some further differentiations of types of manner of motion. The paper is rounded off with three brief case studies from typologically diverse languages, namely Russian, French and Korean.
Gesehen am 07.12.2021